ANTIOXIDANT ACTIVITY AND CURCUMIN LEVELS OF TEMULAWAK (Curcuma xanthorrhiza ROXB.) EXTRACT AND ITS EFFECTS ON BLOOD CELLS IN ALCOHOL-INDUCED WHITE RATS (Rattus norvegicus L.) - Nabila Al – Husnaini; Syukriah Syukriah (Universitas Medan Area, 2026)
Temulawak (Curcuma xanthorrhiza Roxb.) is a traditional Indonesian medicinal plant rich in Curcumin and active compounds such as triterpenoids, alkaloids, saponins, and flavonoids, which exhibit antioxidant and anti-inflammatory properties. Curcumin content was quantified at 109.58 mg/g using the UV-Vis spectrophotometry method, and its antioxidant activity was confirmed through increasing DPPH inhibition percentages with increasing extract concentrations, with the IC₅₀indicating significant radical scavenging potential. Excessive 45% ethanol intake can induce oxidative stress and alter white blood cell counts. This study used 20 male white rats (Rattus norvegicus L.) weighing 180–200 g, divided into normal control, alcohol control, and ginger extract treatment groups at doses of 100, 200, and 300 mg/kg body weight. Hematological parameters observed included erythrocytes, hemoglobin, hematocrit, MCV, MCH, MCHC, platelets, and total and differential leukocyte counts. Results showed that ginger extract, particularly at 200 mg/kg, stabilized blood profiles after alcohol consumption, with hematological values approaching normal levels. Differences between groups were not statistically significant, indicating the safety and antioxidant potential of ginger extract.